Implementación de un sistema de contabilidad de costos por órdenes de producción en la empresa agro-industrial “Aviplasa”, ubicada en la parroquia Belisario Quevedo del cantón Latacunga, provincia de Cotopaxi, en el periodo del 01 de agosto al 31 de diciembre del 2013 - Coronel Velasco, Vicente Daniel (2015)
Speaking of cost accounting, it comes directly to our mind the industrial production, the intervention of material , human and economic factors involved and used will result in a finished good to be consumed or sold; for this propose we establish as main objective the implementation of an accounting cost system for production orders, which is why it was considered to conduct a research in the Agroindustrial company "AVIPLASA" in order to determine the impact on the management of costs production thereof; through research techniques, inductive, deductive methods, tools such as interview and surveys; resulting in the feasibility of implementing this costing system; so it is recommended to run that system.